The Routledge Handbook of Cultural Ecosystem Services - McElwee, Pamela D (Taylor & Francis, 2025)
The Routledge Handbook of Cultural Ecosystem Services provides an overview of Cultural Ecosystem Services (CES), which are the nonmaterial aspects of benefits that people derive from nature. These diverse and multifaceted contributions can include experiences, capabilities, and identities, among others. The Handbook addresses how these CES are valued, how they reflect human-nonhuman relationships, and what roles they can play in improved human well-being, ecosystem management, and trajectories towards sustainability. This Handbook presents a wide array of perspectives on the roles CES can play in understanding relationships to nature, and on how those relationships might translate into policy. The Handbook includes philosophical approaches to CES, typologies and classifications of types of CES, and case studies of places, people, policies and projects engaging CES. Across seven distinctive Parts, the chapters deliver a number of important practical lessons on how to understand, measure, and value CES, and use examples and applications from around the world, including how CES apply across different biomes. The Handbook also includes a selection of compelling artworks that represent CES in different cultural contexts. The 91 authors represent 19 different countries, providing a rich range of experiences, including a strong focus on the Global South. This book can serve as a comprehensive guide to researchers who are new to CES and wish to understand more about the field, and as a set of go-to instructions for experienced CES researchers. It can also inform policymakers who wish to better incorporate CES into their work. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives (CC BY-NC-ND) 4.0 license